Big differences in little people - Hamedanizadeh, F (Iran University of Medical Sciences, 1991)
Extract: Sever coughs of the little Zahra who has 8 months old informed you even before that her parents inter to the ward. Zahra's developmental needs in terms of emotional, physical and social will required a detailed cares in her hospitalization period. But at this time her breathing problem may attracted your attention. Needs and differences of the mentioned infant explain below. Zahra's respiratory rate is 32 per minutes when healthy period which is almost twice than as in adults. Her respiratory rate reflects the high metabolism rate of her body that is necessary for support of her rapid growth